Short term efficacy of recombinant porcine factor VIII in patients with factor VIII inhibitors. Issue 4 (27th April 2020) - Abou‐Ismail, Mouhamed Yazan; Vuyyala, Sowjanya; Prunty, Jeremy; Schmaier, Alvin H.; Nayak, Lalitha
Abstract: Background: Antibodies against factor VIII (FVIII), seen in acquired (AHA) and congenital haemophilia A, lead to severe bleeding diatheses. Current first‐line treatment includes bypass agents. Recombinant porcine sequence FVIII (rpFVIII) was developed as an alternative therapy. Aim: To describe our institutional experience with the use of rpFVIII. Methods: A retrospective chart review of five patients treated with rpVIII between 2016 and 2019. Results: Five patients (four AHA, one congenital haemophilia with inhibitors) were treated with rpFVIII. No patient had an adverse event during infusion. All patients initially exhibited a response evidenced by increased FVIII levels from baseline <1% to 81%‐170%, normalization of the activated partial thromboplastin time (aPTT) and resolution of bleeding. However, all five patients were subsequently noted to have decreasing peak FVIII levels and aPTT prolongation, either within the initial treatment course or upon later re‐administration. Resistance to rpFVIII was recognized after an average of 12.4 exposure days. Porcine FVIII inhibitor levels measured afterwards were present (detectable—170 Bethesda units) in all patients. Three out of four AHA subjects also developed an increase in the anti‐human FVIII inhibitor titres after receiving rpFVIII. Conclusion: rpFVIII was safe and initially effective in all patients. However, its use is associated with development of an inhibitor to rpFVIII, decreasing its efficacy and duration of effect. Further, rpFVIII use may lead to an increase in patient anti‐human FVIII inhibitor titres. A larger study is necessary to appropriately assess the incidence of these outcomes.